The Effect of Digital Marketing Strategy and Service Quality on Customer Satisfaction in the Indonesian E-Commerce Industry - Misidawati, Dwi Novaria; Darmiono, Darmiono; Devi, Erwina Kartika; Fatimah, Siti; Sarwono, Sarwono (Sinergi International Journal of Management and Business, 2023)
This study investigates the influence of digital marketing strategy and service quality on customer satisfaction within the Indonesian e-commerce industry. Driven by the significant growth of e-commerce in Indonesia, the research aims to identify the key factors that impact customer satisfaction and provide actionable insights for e-commerce businesses. Utilizing a quantitative research design, data were collected from 200 Indonesian e-commerce customers through a structured questionnaire. The analysis employs Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to evaluate the relationships between digital marketing strategy, service quality, and customer satisfaction. Results indicate that both digital marketing strategy and service quality positively and significantly affect customer satisfaction. The findings underscore the importance of integrating robust digital marketing tactics and maintaining high service quality to enhance customer satisfaction and loyalty in the competitive e-commerce landscape of Indonesia. These insights offer valuable recommendations for e-commerce companies aiming to improve their customer engagement and service delivery practices.